Hemorragia subaracnoidea y duración prolongada de la cateterización como factores de riesgo de infección relacionada con drenaje ventricular externo. Hospital Regional Docente de Trujillo - Martínez Mendoza, Kelly Jackeline (2020)
Objective: Determine if subarachnoid hemorrhage and prolonged duration of catheterization are risk factors for infection related to external ventricular drainage at Hospital Regional Docente de Trujillo. Method: Analytical, retrospective, longitudinal, and case-control observational study; with a review of clinical histories of patients hospitalized in the neurosurgery service at Hospital Regional Docente de Trujillo during the period January 2009 - December 2018, following strict inclusion and exclusion criteria. Results: The frequency of DVE-related infection is 33.3%, with Staphylococcus epidermidis being the most common pathogen (54%). Subarachnoid hemorrhage was found to lead to a significantly higher risk of infection related to DVE [OR = 4.75; 95% CI (1.96 - 11.52); p = 0.0004]. Similarly, the prolonged duration of catheterization longer than 5 days has a significant high risk [OR = 5.93; 95% CI (1.65 - 21.32); p = 0.0030]. Conclusion: Subarachnoid hemorrhage and prolonged duration of catheterization are risk factors for infection related to external ventricular drainage at Hospital Regional Docente de Trujillo.